Wintrobe's atlas of clinical hematology - Weksler, Babette B., ....-; Schechter, Geraldine P., ....-; Ely, Scott A., ....- ([s.l.] : Wolters Kluwer, 2018)
Featuring over 400 brilliantly sharp, high-resolution diagnostic digital photomicrographs combined with concise, clinically oriented text, this full-color atlas is a comprehensive pictorial guide to diagnostic hematology. Tied to the classic and world-renowned textbook Wintrobe's Clinical Hematology, this brand-new atlas enables physicians to see and readily comprehend diseased tissues and understand the complex assays routinely used in the care of patients with hematologic diseases.The comprehensive pictorial collection includes relevant clinical and radiological images accompanied by photomicrographs (surgical and autopsy specimens), and advanced diagnostic laboratory images that include molecular assays, FISH, and cytogenetics. All the major diseases in Wintrobe's and all the major hematolymphoid disorders recognized by the World Health Organization are included in this comprehensive collection of diagnostic images. The color pictures are combined with diagrams and tables that help readers use "algorithmic
Hematologie